2016
DOI: 10.4155/fmc-2016-0084
|View full text |Cite
|
Sign up to set email alerts
|

How can We Address the Controversies Surrounding the Use of Nsaids in Neurodegeneration?

Abstract: How can we address the controversies surrounding the use of NSAIDS in neurodegeneration?"We propose developing transgenic mouse and hybrid enzyme constructs as a research platform to help further our understanding of NSAIDs and their potential application in this pathology."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Pharmacological treatments, therefore, should intend to reduce this inflammatory response. Curiously, so far, interventions with anti-inflammatory drugs in patients suffering from these disorders did not result in successful treatments (Gilgun-Sherki et al 2006;Hernan et al 2006;McGeer and McGeer 2007;Schwartz and Ziv 2008;Schwartz and Shechter 2010;Ling et al 2016). In patients suffering acute neurodegeneration such as spinal cord injuries, in which secondary inflammatory processes are mainly responsible for final clinical outcome, initially it was suggested that methylprednisolone (MP) did significantly reduce disability, though this could not be confirmed in later studies, and side effects appeared to outweigh any beneficial effects (Hurlbert 2000;Bracken 2012).…”
Section: Anti-inflammatory Drug Interventions In Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological treatments, therefore, should intend to reduce this inflammatory response. Curiously, so far, interventions with anti-inflammatory drugs in patients suffering from these disorders did not result in successful treatments (Gilgun-Sherki et al 2006;Hernan et al 2006;McGeer and McGeer 2007;Schwartz and Ziv 2008;Schwartz and Shechter 2010;Ling et al 2016). In patients suffering acute neurodegeneration such as spinal cord injuries, in which secondary inflammatory processes are mainly responsible for final clinical outcome, initially it was suggested that methylprednisolone (MP) did significantly reduce disability, though this could not be confirmed in later studies, and side effects appeared to outweigh any beneficial effects (Hurlbert 2000;Bracken 2012).…”
Section: Anti-inflammatory Drug Interventions In Neurodegenerationmentioning
confidence: 99%
“…Recent discoveries in these diseases, though, have demonstrated the presence of inflammation propagating substrates, and trials with several potential 1 3 immune-modulating therapies provided increasing evidence that primary induced apoptosis followed by secondary inflammation are heavily involved in the pathogenesis not only in acute but also in chronic neurodegenerative diseases. Although steroidal and non-steroidal anti-inflammatory drugs (N)SAIDs, with their anti-inflammatory effects, as well as various neurotrophic factors, with their pro-survival signaling mechanisms, in the past had been proven to be effective in attenuating neuronal death in many in vitro and in vivo models of neurodegeneration, all larger phase II/ III trials with both (N)SAIDs and/or various neurotrophic factors, so far, did bring equivocal and/or worse outcomes (Gilgun-Sherki et al 2006;Hernan et al 2006;McGeer and McGeer 2007;Schwartz and Ziv 2008;Schwartz and Shechter 2010;Bracken 2012;Ling et al 2016). Maybe wrong timing of administration, nonselective inhibition of COX-2 or Rho-A, sub-optimal dose in target site, or limited penetration to the brain through the blood-brain barrier here may have played a role.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, all larger preclinical and clinical phase II/III trials in acute and chronic neurodegenerative disorders with (N)SAIDs (non-steroidal and steroidal anti-inflammatory drugs), compounds that target inflammatory mechanisms and associated cascades (including thalidomide, selective cyclooxygenase-2 inhibitors such as Celecoxib, cyclophosphamide, cyclosporine, caspase-reducing drugs, and various neurotrophic factors) so far did only bring equivocal and/or worse outcomes (Gilgun-Sherki, Melamed et al 2006, Hernan, Logroscino et al 2006, Gordon, Moore et al 2007, McGeer and McGeer 2007, Schwartz and Ziv 2008, Calvo, Moglia et al 2010, Schwartz and Shechter 2010, Bracken 2012, Rosado, Lavor et al 2014, Ling, Murdoch et al 2016, Collins and Bowser 2017, Fehlings, Wilson et al 2017, Ulndreaj, Badner et al 2017. Maybe wrong timing of administration, nonselective inhibition of cyclooxygenase(COX)-2 inhibitors or Rho-associated protein kinases, sub-optimal dose in target site, or limited penetration to the brain through the blood-brain barrier here may have played a role in the failed approaches (Lossinsky and Shivers 2004, Stamatovic, Keep et al 2008, Gabathuler 2010.…”
Section: Interventions In Neurodegenerationmentioning
confidence: 99%
“…Pharmacological treatments therefore should intend to reduce this inflammatory response. Curiously, so far, interventions with anti-inflammatory drugs in patients suffering these disorders did not result in successful treatments (Gilgun-Sherki, Melamed et al 2006, Hernan, Logroscino et al 2006, McGeer and McGeer 2007, Schwartz and Ziv 2008, Schwartz and Shechter 2010, Ling, Murdoch et al 2016. In patients suffering acute neurodegeneration such as spinal cord injuries, in which secondary inflammatory processes are mainly responsible for final clinical outcome, initially it was suggested that methylprednisolone (MP) did significantly reduce disability, though this could not be confirmed in later studies, and side effects appeared to outweigh any beneficial effects (Hurlbert 2000, Bracken 2012).…”
Section: Anti-inflammatory Drug-interventions In Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation